Bridging the southern gap: first definitive evidence of Late Jurassic ichthyosaurs from Antarctica and their dispersion routes - Campos, Lisandro (2021)
Fil: Campos, Lisandro. División Paleontología Vertebrados, Unidades de Investigación Anexo Museo, Facultad de Ciencias, Naturales y Museo. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET). Argentina.